Прокуратура України як учасник кримінально-виконавчих правовідносин - Дудко, Є.; Dudko, E. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2014)
В статті, на основі з’ясування соціально-правової природи правового статусу прокуратури України та змісту кримінально-виконавчих правовідносин, визначені проблемні питання. В обов’язковому порядку прокурорському нагляду підлягають стан дисципліни та злочинності серед персоналу установ попереднього ув'язнення, ставлення до ув'язнених, виявлення фактів приниження їх людської гідності, незаконного застосування дисциплінарних стягнень, заходів фізичного впливу, спеціальних засобів, вогнепальної зброї, протиправні неслужбові стосунки з особами, взятими під варту, або з їхніми родичами, корупційні зв’язки. Розроблені науково обґрунтовані рекомендації та пропозиції щодо вдосконалення чинного законодавства та практики його застосування. Prosecutor may reveal violations of the law by checking compliance with the laws by visiting places of detention and acquaintance with the procedural documents, on the basis of which arrested persons are contained; surveying during circumvention of detained persons taken into custody, and convicted persons; verifying the legitimacy of orders, instructions and regulations of pre-trial detention’s administration; receiving and reviewing applications and complaints of detained and convicted persons; checking the timeliness and correctness enforcement of sentences by pre-trial detention’s administration; participation in the court trials when considering issues, related to the execution of the sentence. It is mandatory to the prosecutor's supervision the subject of state discipline and crime among the pre-trial detention personnel, treatment of prisoners, revealing the facts of humiliation of their human dignity, unlawful using of disciplinary measures, physical force, special means and firearms, illegal unofficial relations with persons, taken under custody, or their relatives, corrupt relations. Finding acts that contradict to the demands of the law about regime and conditions of detention, the prosecutor must stop the execution of such acts, and then protest them in accordance with the law. In the Criminal Procedural Code the period is not specified, within which the prosecutor informs about the detention of the person, that’s why the author of the article proposes to set a time limit, which will effectively ensure urgent notification.
Prosecutor’s Office of Ukraine as a Member of the Penal Legal Relations.
Keywords: прокуратура; кримінально-виконавчі правовідносини; органи та установи виконання покарань; форми та засоби прокурорського реагування; правопорушення; prosecutor; criminal-executive relationship; bodies and agencies of penal institutions; forms and means of prosecutorial response; offense